Pengembangan Hutan Literasi Sekolah Berbasis Teknologi dalam Mendukung SDGs - Ridwan, Irwan Muhammad; Surahman, Endang; Susanti, Ernita; Sulistyaningsih, Dwi; Makiyah, Yanti Sofi; Maulidah, Rifa’atul; Sumantri, Agus (Sahira Publishing, 2025)
21st-century education demands the development of literacy skills, technology utilization, and environmental awareness. One innovation that integrates these three aspects is the development of a School Literacy Forest, a nature-based learning space that integrates literacy activities and environmental education. SMP Islam Nurul Yaqin in Sodonghilir Sub-District, Tasikmalaya Regency has pioneered the